ENHANCING RETAKAFUL AND CAPITAL EFFICIENCY AND EFFECTIVENESS THROUGH FORMULATION OF OPTIMUM RETENTION - Wan Zamri Wan Ismail; Mohd Faiz Mohamed Yusof; Ismail Ahmad (International Journal of Accounting, Finance and Business, 2021)
The objective of this research is to highlight need for a takaful operator to enhanceefficiency and effectiveness of its retakaful undertakings through the formulation of an optimumretention policy of the takaful risks underwritten before placement to retakaful. This is aqualitative study which discusses the theoretical and practical aspects of retakaful managementwith special reference to retention methodology through literature review and secondary datafrom published sources. This study highlights the practices of retakaful management in orderto optimise risk retention by takaful operators. It outlines the theory and practice of riskretention undertaken in takaful business as a means to heighten the security, sustainability andgrowth of the Participants’ Risk Fund (PRF). This study contributes to the current dearth onliterature and research on takaful and retakaful as a nascent industry, as compared to the morematured insurance and reinsurance industry. Hence, the conventional reinsurancemanagement and practice is also referred as a benchmark. The study would provide betterinsight for the takaful industry in undertaking the retakaful management through a moreefficient and effective retention methodology; supported by practical examples. Betterunderstanding and management of retakaful in terms of retention policy by takaful operatorsbased on a practitioner’s perspective in order to bolstering the technical and financial positionof the PRF.